Case Report: Terapi Massage Efflurage Dengan Virgin Coconut Oil (VCO) Terhadap Pencegahan Risiko Dekubitus Pada Lansia Bedrest - Milawanti Hasan; Nina Dwi Lestari (Pusat Riset dan Inovasi Nasional, 2023)
Decubitus or pressure sores are conditions that occur due to pressure, friction or a combination of pressure and strain on protruding bone areas, this can occur in the elderly who experience bedrest or limited mobility. Objective: To apply massage efflurage intervention with virgin coconut oil (VCO) to the risk of decubitus of bedrest patients. Methods: The method in this study was used a case report with massage efflurage intervention with virgin coconut oil in elderly bedrest patients, carried out for 3 days. Result: The results of this case study showed that after efflurage massage with virgin coconut oil, the risk of decubitus decreased from high risk to medium risk. Conclusion: Massage efflurage therapy with virgin coconut oil is effective in preventing decubitus in elderly people who experience limited mobilization